Conditions required to ensure successful detection and management of mild cognitive impairment in primary care: A Delphi consultation study in China - Yuan Lu; Yuan Lu; Yuan Lu; Yuan Lu; Chaojie Liu; Dehua Yu; Dehua Yu; Dehua Yu; Yvonne Wells (Frontiers Media S.A., 2022)
ObjectiveDetection and management of mild cognitive impairment (MCI) in primary care has been recognized internationally as one of the strategies that can be employed to delay the development of dementia. However, little is known about what role primary care should play. This study aimed to develop a checklist of conditions necessary for successfully detecting and managing mild cognitive impairment in primary care in China.MethodsThis study employed the Delphi method to establish expert consensus on the conditions required for successfully detecting and managing MCI in primary care in China. Twenty-four experts who specialized in general practice, public health, neuropsychology, or community health service management rated the importance of pre-defined conditions (44 items measuring providers' preparedness, patient engagement, and system support in line with the Chronic Care Model). The degree of consensus among the experts was measured using four indicators: median ≥ 4, mean ≥3.5, Co-efficient of Variance < 0.25, and retention in the checklist required ≥ 80% agreement with a rating of important or essential. The checklist and descriptions of the conditions were revised according to the experts' feedback and then sent out for repeated consultations along with a summary of the results of the previous round of consultations. Consensus was achieved after the second round of consultations, which was completed by 22 of the experts.ResultsThe experts endorsed a checklist of 47 conditions required for successful detection and management of MCI in primary care in China. These conditions were categorized into four domains: prepared general practitioners (17 items), engaged patients (15 items), organizational efforts (11 items), and environmental support (4 items).ConclusionsSuccessful detection and management of MCI in primary care in China requires a dedicated and competent workforce of general practitioners, as well as the engagement of patients and family caregivers. Adequate support from healthcare organizations, health system arrangements, and the broader society is needed to enable effective interactions between general practitioners and patients and efficient delivery of the services required to detect and manage MCI.